A Crank-Nicolson Method of Autocatalytic Reaction-Diffusion Systems - Abbas Al-Bayati; Saad Manaa; Abdulghafor Al-Rozbayani (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper we used two numerical methods to investigate propagating heat solutions of PDEs. The explicit and Crank-Nicolson methods and the results show that Crank-Nicolson method is more accurate than the explicit method. As an illustration, we used the above method to an autocatalytic reaction diffusion equations involving two diffusing chemicals in one dimension.